Peran dan Kendala Orang Tua dalam Mendampingi Anak Belajar dari Rumah pada Masa Pandemi Covid-19 di RT 008 RW 03 Kelurahan Semanan Jakarta Barat - Ariyani, Silva; Nurhayati, Siti; Saputri, Rahmawati Eka (Lembaga Yasin AlSys, 2022)
The purpose of this study was to determine the role and constraints of parents in assisting children to learn from home during the Covid-19 pandemic at RT 008 RW 03 Semanan Village, West Jakarta. This research uses descriptive qualitative research. The subjects in this study were 13 students’ parents. With data collection techniques through observation, interviews, and documentation. The result showed that (1)the role of parents in online learning are: (a) As a motivator, namely giving praise and gifts. (b) As a facilittaor, parents provide needs during onlibe learning. (c) As a mentor, namely parents as well as teacher when children face material difficulties. (2) the obstacles faced by parents are the lack of ubderstanding of the material by parents, the difficulty of parents in fulfilling online learning facilities, the lack of patience of parents in accompanying their children, the difficulties of parents in growing their children’s interest in learning, and the lack of time in accompanying their children.